The measurement of environmental and resource values theory and methods - Freeman, A. Myrick III 1936-; Herriges, Joseph A. 1956-; Kling, Catherine L. (RFF Press, 2014)
"The first edition of this important work was the winner of the 2002 Publication of Enduring Quality award by the Association of Environmental and Resource Economists. The continuing premise for the book is that estimates of the economic values of environmental and natural resource services are essential for effective policy-making. As previous editions, the third edition, which includes two additional co-authors, presents a comprehensive treatment of the theory and methods involved in estimating environmental benefits"--Provided by publisher.